Dissolution of marriage on the ground of cruelty : a comparative overview of fasakh and irretrievable breakdown of marriage principles - Abas, Afridah; Md Hashim, Noraini; Abdul Hak, Nora (INSI Publications, 2012)
In Islam, if a husband treats his wife with cruelty either physically or mentally, she has the right to apply to the court for the marriage to be dissolved on the ground of fasakh. In Malaysia, the practice is that the Syariah (In Malay language, Shari‘ah is known as Syariah) Court asks the wife to provide sufficient evidence to prove her claim, failure of which the application for fasakh will be set aside. In some cases, a Syariah Court demands a high standard of proof of the act of cruelty by the husband such as the requirement of two male witnesses, who have witnessed such act. This has caused difficulty to the wife, as it is practically hard to fulfil this requirement. Whilst, under section 54 (1) (b) of the Law Reform (Marriage & Divorce) Act, 1976, the plaintiff may petition for divorce on the ground that the respondent has behaved in such a way that the plaintiff cannot be reasonably be expected to live with the respondent. The act of cruelty of the respondent either physically or mentally is more than adequate to the term behaviour as stated under the present divorce law. In the case of irretrievable breakdown of marriage, both the objective and subjective tests have been used by the courts to decide whether or not the plaintiff can reasonably be expected to live with the respondent as a consequence of the respondent’s behaviour, including, cruelty. If it is proven, then the court will grant the application for divorce. This article examines the above issues relating to the methods of proof and evidentiary requirement in cruelty cases. Relevant legal provisions as provided under the Malaysian laws i.e., the LRA 1976 and the Islamic Family Law Act/Enactments and the practice of the Malaysian courts relating to this issue are also examined. Decisions of the Syariah and Civil Courts on cruelty in divorce cases are analysed to highlight the practice in Malaysia.